Thermodilution vs indirect fick cardiac output measurement in clinical practice: insights from a tertiary centre. (25th November 2020) - Pereira, A; Santos, J.G; Loureiro, M.J; Ferreira, F; Almeida, A.R; Cale, R; Repolho, D; Vitorino, S; Morgado, J; Pereira, H
Abstract: Introduction: Thermodilution (TD) and indirect Fick (IF) methods are widely used to measure cardiac output (CO). They are often used interchangeably to make critical clinical decisions, yet few studies have compared these approaches concerning agreement and comparative prognostic value as applied in medical practice. Purpose: To assess agreement between TD and IF methods and to compare how well these methods predict mortality. Methods: Retrospective cohort study including all consecutive right heart catheterizations performed in a referral pulmonary hypertension (PH) centre from 2010 to 2018. Cardiac index (CI) was calculated by indexed CO to body surface area. PH was classified according to the new definition of the 6st World Symposium on Pulmonary Hypertension 2018 [mean pulmonary arterial pressure (mPAP) >20 mmHg]. Patients with cardiac or extra-cardiac shunts or significant (moderate to severe or severe) tricuspid regurgitation were excluded. All-cause mortality over 1 year after right heart catheterization was recorded. Logistic regression was used to identify predictors of the adverse event. Results: From a total of 569 procedures, 424 fulfilled the inclusion criteria: mean age 56.7±15.4 years, 67.3% female. Haemodynamic parameters were diagnosed of PH in 86.2% of cases: mPAP 35.3±15.3 mmHg, 83.6% pre-capillary subtype, 42.9% belonging to group 4 (chronic thromboembolic pulmonary hypertension) and 26.6% to group 1 (pulmonary arterial hypertension). Mean values of CO and CI were, respectively, 4.5±2.8 L/min and 2.5±0.8 L/min/m 2 measured by TD and 4.6±2.4 L/min and 2.6±1.3 L/min/m 2 measured by IF method. There was a median difference (IF minus TD) of - 0.03 / min to CO and - 0.05 L/min/m 2 to CI but both meausres correlated only modestly (r=0.6 to TD and r=0.5 to IF). One-year all-cause mortality rate was 5.4% (median time to death was 50.5 days). Lower values of CO and CI assessed by TD were significantly associated with all-cause mortality occurrence (CO TD: 4.5±1.3 L/min versus 3.6±1.0 L/min, p<0.01; CI TD: 2.6±0.7 L/min/m 2 versus 2.1±0.4 L/min/m 2, p<0.01). No association was observed between CO (p=0.31) and CI (p=0.42) measured by IF method and the adverse event. Logistic regression identified 2 independent predictors of all-cause mortality: TD CO (OR 0.55, 95% CI 0.38–0.79, p<0.01) and TD CI (OR 0.34, 95% CI 0.17–0.67, p<0.01). Similar results were obtained when patients diagnosed with PH were independently analyzed. Conclusions: There is only modest agreement between TD and IF CO and CI estimates. Despite being more time-consuming, TD measurements were predictors of all-cause mortality and present a highest prognostic value. These findings favored their used over IF in clinical practice. Funding Acknowledgement: Type of funding source: None